A new fibre bridging based analysis of the Double Cantilever Beam (DCB) test - Morais, A.B. de
A new analysis was developed for the Double Cantilever Beam (DCB) test. Its main objective is to compute mode I critical strain energy release rates GIc unaffected by fibre bridging. In fact, the latter phenomenon often observed in standard unidirectional specimens is not considered representative of most structural applications. The analysis developed applies a relatively simple numerical procedure to experimental load -displacement data for the initial crack propagation stages. Moreover, it does not require monitoring crack propagation during the tests. Application to experimental data for carbon and glass fibre composites gave consistent propagation GIc that were similar to initiation values, thereby supporting the main assumptions of the proposed model.